PENYETARAAN GENDER DALAM HAL PEMBAGIAN WARISAN - Amalia, Endah Amalia (Ahkam: Jurnal Hukum Islam, 2020)
Inheritance is the transfer of property owned by someone who has died and then given to someone else who has the right to inherit it. Sons should inherit more shares than daughters. But along with the development of an increasingly advanced era, there is a phenomenon of equal distribution of inheritance between sons and daughters. Under the pretext of gender equality, and emancipation of women, it is fair. This research was conducted to find out the views of Islamic law regarding the equal distribution of inheritance between sons and daughters. This research uses qualitative analysis using the literature study method. This research found that gender equality in the distribution of inheritance occurs with the times and its implementation still adheres to the applicable Islamic law. The differences in the distribution of inheritance between men and women are not caused by gender difference, but the differences in responsibilities imposed on men more than women. Keywords: Equal, Gender, Inheritance.